HealthXStream: A Privacy Focused Doctor Meetup Solution for the General Public - Dissanayake, S; Jayamanne, D (NSBM Green University, 2018)
“HealthXStream” is a privacy oriented, fully secure, health monitoring platform where patients and doctors get connected with each other to solve non-severe health problems. There are very few software applications in the world providing consumer grade doctor meetups through the mobile phone. Even from that few, “HealthXStream” being unique as it provides the real-time pulse rate and the temperature while providing the privacy at its peak. And it is the only health monitoring application with privacy in mind which complies to the European legislations. Doctors and the Patients are the main actors where the patients could chat with the doctor, while the pulse rate/body temperature streamed. This solution is mainly targeted to people in senility and for the people who are not preferring to move outside to meet the doctor. This will address the issue of inconvenience in accessing the doctor in a senility environment where privacy and security matters.
Keywords: AWS; Android; Arduino; Doctor Channeling; EU GDPR; Health Monitoring; IoT; MQTT; Privacy; Security